1987
DOI: 10.1080/08858198709527853
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal initiation of smokeless tobacco usage: Implications for cancer education

Abstract: One hundred fifty (150) randomly chosen adult male subjects (average age 37) drawn from a university general dental clinic were classified by self-report into three equal categories of fifty smokeless tobacco users, fifty cigarette smokers (non-smokeless tobacco users), and fifty non-tobacco users. According to questionnaire results, a bimodal curve was exhibited among smokeless tobacco users with the two peaks of initiation at ages 12 and 18 compared to a unimodal age of initiation for cigarette smokers at ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…For older initiators, particularly high school and college students, educational efforts should be aimed at understanding the role of peer influence and enlisting peers, coaches, and community role models in prevention programs [47]. Five recent studies appear to corroborate these findings, indicating differences between urban versus rural localities and age of initiation [48,50-531. Thus, with the re-emergence of smokeless tobacco in the 1970s, the nature of the males initiating this habit appear to have changed [54].…”
Section: Educational Interventionsmentioning
confidence: 74%
See 1 more Smart Citation
“…For older initiators, particularly high school and college students, educational efforts should be aimed at understanding the role of peer influence and enlisting peers, coaches, and community role models in prevention programs [47]. Five recent studies appear to corroborate these findings, indicating differences between urban versus rural localities and age of initiation [48,50-531. Thus, with the re-emergence of smokeless tobacco in the 1970s, the nature of the males initiating this habit appear to have changed [54].…”
Section: Educational Interventionsmentioning
confidence: 74%
“…The educational strategy for prior to twelve years of age for primarily rural boys, should be directed toward family, parents and siblings to provide a supportive environment. The educational strategy for the high risk cohort peaking at eighteen, of primarily nonrural boys, should be directed to the boys' friends to provide a supportive environment [47]. Just as in anti-smoking attempts, current health education efforts may be starting too late.…”
Section: Educational Interventionsmentioning
confidence: 98%
“…Passive advertising still has an impact, even though smokeless tobacco has been banned from commercials (54). One study (49) not only indicated the influence that peers and family members could have with regard to the use of smokeless tobacco, bu t also indicated varying influences depending on urban or rural dwelling. This is probably related in part to social history and varying levels of acceptability.…”
Section: Dental Practitioners' Influence As Role Models For Patients mentioning
confidence: 99%
“…Although smokeless tobacco users have been known to begin their habit as early as age 5, a bimodal curve has been observed showing two high-risk groups, peaking around ages 12 and 18 (49). The younger initiators are primarily from rural communities, having a strong parental or familial influence for initiating smokeless tobacco use.…”
Section: Dental Practitioners' Influence As Role Models For Patients mentioning
confidence: 99%
See 1 more Smart Citation